1998
DOI: 10.1074/jbc.273.4.2288
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the in Situ Activity of Tissue Transglutaminase by Calcium and GTP

Abstract: Tissue transglutaminase (tTG) is a calcium-dependent enzyme that catalyzes the posttranslational modification of proteins by transamidation of specific polypeptide-bound glutamine residues. Previous in vitro studies have demonstrated that the transamidating activity of tTG requires calcium and is inhibited by GTP. To investigate the endogenous regulation of tTG, a quantitative in situ transglutaminase (TG) activity assay was developed. Treatment of human neuroblastoma SH-SY5Y cells with retinoic acid (RA) resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(198 citation statements)
references
References 59 publications
(64 reference statements)
5
192
1
Order By: Relevance
“…5-HT2A receptor-mediated incorporation of 5-HT into the small GTPases RhoA and Rab4 has also been observed in platelets (Walther et al, 2003). It was suggested that 5-HT2A and muscarinic receptor-mediated release of Ca 2+ from intracellular Ca 2+ stores may be responsible for triggering TG transamidating activity (Zhang et al, 1998;Walther et al, 2003). Our recent studies have shown that the Gi/o-protein coupled A1 adenosine receptor stimulates TG2 activation in H9c2 cardiomyocyte-like cells (Vyas et al, 2016).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 90%
See 3 more Smart Citations
“…5-HT2A receptor-mediated incorporation of 5-HT into the small GTPases RhoA and Rab4 has also been observed in platelets (Walther et al, 2003). It was suggested that 5-HT2A and muscarinic receptor-mediated release of Ca 2+ from intracellular Ca 2+ stores may be responsible for triggering TG transamidating activity (Zhang et al, 1998;Walther et al, 2003). Our recent studies have shown that the Gi/o-protein coupled A1 adenosine receptor stimulates TG2 activation in H9c2 cardiomyocyte-like cells (Vyas et al, 2016).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 90%
“…Previous studies have shown that release of Ca 2+ from intracellular Ca 2+ stores or influx of extracellular Ca 2+ is linked to TG activation in response to GPCR stimulation (Zhang et al, 1998;Walther et al, 2003;Vyas et al, 2016 et al, 2011).…”
Section: Role Of Ca 2+ In Pac1 Receptor-mediated Tg2 Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose-response experiments demonstrated that the effects of TGF-b1 on TG2 expression occur from concentrations of 0.5-5 ng/ml of TGF-b1 (Supplementary Figure 1e), ranging within physiological limits. The enzymatic function of TG2 was also induced by TGF-b1, as measured by amine incorporation into total cellular proteins (Zhang et al, 1998). Increased TG2 activity was observed in OC cells (Hey and OVCA#16), but not in non-transformed LP9 or NOSE cells (Supplementary Figure 2).…”
Section: Tgf-b1 Induces Tg2 Expression and Function In Oc Cellsmentioning
confidence: 95%